Ultrasonic Spray-Coating of Large-Scale TiO2 Compact Layer for Efficient Flexible Perovskite Solar Cells - Peng Zhou (Micromachines, 2017)
Flexible electronics have attracted great interest in applications for the wearable devices. Flexible solar cells can be integrated into the flexible electronics as the power source for the wearable devices. In this work, an ultrasonic spray-coating method was employed to deposit TiO2 nanoparticles on polymer substrates for the fabrication of flexible perovskite solar cells (PSCs). Pre-synthesized TiO2 nanoparticles were first dispersed in ethanol to prepare the precursor solutions with different concentrations (0.5 mg/mL, 1.0 mg/mL, 2.0 mg/mL) and then sprayed onto the conductive substrates to produce compact TiO2 films with different thicknesses (from 30 nm to 150 nm). The effect of the different drying processes on the quality of the compact TiO2 film was studied. In order to further improve the film quality, titanium diisopropoxide bis(acetylacetonate) (TAA) was added into the TiO2-ethanol solution at a mole ratio of 1.0 mol % with respect to the TiO2 content. The final prepared PSC devices showed a power conversion efficiency (PCE) of 14.32% based on the indium doped tin oxide coated glass (ITO-glass) substrate and 10.87% on the indium doped tin oxide coated polyethylene naphthalate (ITO-PEN) flexible substrate.